A spanyol baloldali pártok programjai az 1936. februári választás előtt - Harsányi, Iván (Acta Scientiarum Socialium, 2015)
Programs of the Spanish Left Wing Parties on the Eve of the 1936 Parliamentary Elections In the months before the elections this parties prepared programs presenting their inmediate, and some of their long-term goals, reacting to one another in the process. The worker and the bourgeois-democratic republican parties tried to overcome their disagreements in order to form a wide common block facing the similarly fragmented right parties. While the programs of the worker parties featured more radical ideas, the bourgeois-democratic document focused primarily on the reconstruction of the constitutional achievments of the 1931-1933 socialist–republican government. In the end, the common program backed by numerous organizations contained overhelming the goals of the buorgeois democratic parties, referring to the differences between the parties. This proved to be sufficient for winning by a wide margin.
Keywords: left-wing parties; parliamentary elections; common program; worker parties; bourgeois-democratic parties